Multiple Sclerosis Diagnosis and Treatment - Rivera, Víctor M. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Multiple sclerosis (MS) offers important challenges to understanding its complex genetics and molecular and immunological mechanisms, which eventually lead to relapsing and progressive clinical forms and a constellation of clinical manifestations. Along with the progress in knowledge, disease-modifying treatments and new therapeutic molecules have made an impact on the prognosis of the disease. Essential in the diagnostic identification process of MS is the differentiation of this major demyelinating disease with other inflammatory CNS disorders, including Neuromyelitis Optica and MOG antibody disease. MS is more prevalent in women; therefore, pregnancy and post-partum hormonal and immunological changes typically affect the clinical behavior of the disease. This Special Issue of Biomedicines addresses recent advances in the mechanistic genetic and immunological processes of MS, opening more options to future studies and to the consideration of further therapeutic possibilities. The issue discusses the application of modern therapies, including monoclonal antibodies, some still in the process of complete development, and the current strategies managing progressive MS. The aim of this issue is to stimulate basic and clinical research and promote observations on the ever-expanding and complex field of MS. Advancement in the understanding of the mechanisms and the clinical characterizations of this disease should result in improved therapeutic outcomes that reduce neurological and cognitive disability commonly associated with progressive disease.